Juridical comparative analysis of delegating of authority of bodies of executive power to bodies of local self-government in Ukraine and countries-members of the EU - Новак, А. О. (Theory and practice of jurisprudence, 2016)
Problem setting: Development of up-to-date constitutional and legal model of the institute of local self-governance in Ukraine is accompanied by a significant number of problems, related to delegating of state authority to bodies of local selfgovernment. For proper resolution of these problems, it is appropriate to learn about how similar issues were solved in other countries. Recent research and publications analysis: Certain aspects of interaction of bodies of state and local self-government authorities, problems of delegating of state authority to local governments in the context of world and Ukrainian practice have been reflected in scientific developments of O.V. Batanov, V.I.Bordeniuk, Y.V. Deliia, A.R. Krusian and others. Paper objective: analysis of practices of countries-EU members concerning the grounds and order of delegating of specific authority of state power to bodies of local self-government, organization of its realization and control of its implementation, development of proposals of adoption of better practices in the sphere of municipal management in Ukraine. Paper main body: In political and legal practice of European countries there are used different methods of interaction of bodies of state power and local governments, specifics of which is conditioned first of all by one or another system of local management. State governance authority delegated to the bodies of local self-government in Ukraine and European countries is considered as such, that preserves its state and legal character. (But delegation of authority serves the goal of decentralization of public power, making mechanism of providing of public services more available to citizens and increase of efficiency of municipal management.) Legislation of European countries provides for maximal separation of areas of responsibility of bodies of state executive authority and bodies of local selfgovernment. Local bodies of state governance, which names vary depending on a country, have authority mainly within the framework of the questions, which belong to the sphere of competence of the state. Bodies of state power control both implementation of the delegated authority and use of the forwarded means and resources, they are vested the right to give instructions concerning realization of the authority. Conclusion of the research: Adoption of the best practices of European countries in the sphere of delegating of authority is possible exclusively through legal methods. To reach this objective the following steps are suggested: first, adopting amendments to the laws in force of Ukraine, in particular to the laws of Ukraine “About Local Self-Governance In Ukraine” and “About Local State Administrations”; second, passing the law specifically dealing with delegating of authority; third, codification of the legislation concerning local self-governance and elimination of its contradictions and gaps. This will contribute to development of the necessary grounds for optimization of interaction of bodies of local self-government and bodies of state authority, prevention of conflict of competences between them, increase of efficiency of municipal management and implementation of European standards and better practices of the EU states in the sphere of delegating of authority.